Be afraid : tales of horror - Van Belkom, Edo. (Plattsburgh, N.Y. : Tundra Books of Northern New York, 2000)
Fifteen tales of horror by fifteen different writers, drawn from real life experiences.
"McClelland & Stewart Young Readers"--T.p. verso.
Book Links (A.L.A.).
School Library Journal.
Voice of Youth Advocates (V.O.Y.A.).
Young Adult
Keywords: Horror stories; Short stories; Horror fiction; Short stories